2 pair of genes 23 genes in a pair so 23x2= 46
x = -1.2153 x = 2.0614
(3x + 1)(4x - 1)(x - 2)
23x2=46 A human somatic cell contains 46 chromosomes
one mole sodium carbonate contains 23X2 sodium, for three moles it will be 23X2X3=138 gram;
Equations don't equal numbers. An equation is a statement that has mathematicaloperations and possibly numbers in it.There are an infinite number of equations for which 46 could be a solution.Here are a few:x + 2 = 48100 - x = 54x/2 = 23x2 - 2,116 = 010x/10 = 39,810.717
The pattern is twice the previous number plus 1 * 2 * (2x2)+1 = 5 * (5x2)+1 = 11 * (11x2)+1 = 23 * (23x2)+1 = 47
(21x3-23x2-76x-32)/(7x+4) = [3x2(7x4) -5x(7x+4)-8(7x+4)]/(7x+4)=3x2-5x-8
The factors of 23x2 are: 1, 23, x, x2, 23x, and 23x2.
Atomic mass of sodium is 23. The atomic mass of oxygen is 16. Therefore the molecular mass of sodium oxide is 23x2+16=62u.The atomic mass of oxygen is 16. Atomic mass of sodium is 23. Therefore the molecular mass of the given compound is 62 grams per mole.
either to much or to little! LMAO!! <3333 I hAte science so i don't really care!! Find the answer yourself! the Answer is 23 chromatids and at the end of inter phase there should be 46 23x2=46 answer posted at 11:40 may 6 2009 by___________
If atomic masses, Na = 23 C=12, O = 16 Molar mass of Na2CO3 = (23x2) + 12 + (16 x 3) = 106 mass of Na in this compound = 2x23 = 46 Therefore percentage = 46 / 106 x 100 = 43.4%
4623x2Since 2 is a prime number and so is 23 we can go no further.If 23 could be factored, we would put its factors on the next line. We would keep going until we had all primes. It is not possible to write it in tree form here, so we left justify it.
The X chromosome is one of the two sex chromosomes in humans (the other is the Y chromosome). The sex chromosomes form one of the 23 pairs of human chromosomes in each cell. The X chromosome spans about 155 million DNA building blocks (base pairs) and represents approximately 5 percent of the total DNA in cells. Each person normally has one pair of sex chromosomes in each cell. Females have two X chromosomes, while males have one X and one Y chromosome. Early in embryonic development in females, one of the two X chromosomes is randomly and permanently inactivated in cells other than egg cells. This phenomenon is called X-inactivation or Lyonization. X-inactivation ensures that females, like males, have one functional copy of the X chromosome in each body cell. Because X-inactivation is random, in normal females the X chromosome inherited from the mother is active in some cells, and the X chromosome inherited from the father is active in other cells. Some genes on the X chromosome escape X-inactivation. Many of these genes are located at the ends of each arm of the X chromosome in areas known as the pseudoautosomal regions. Although many genes are unique to the X chromosome, genes in the pseudoautosomal regions are present on both sex chromosomes. As a result, men and women each have two functional copies of these genes. Many genes in the pseudoautosomal regions are essential for normal development. Identifying genes on each chromosome is an active area of genetic research. Because researchers use different approaches to predict the number of genes on each chromosome, the estimated number of genes varies. The X chromosome likely contains between 900 and 1,400 genes. These genes perform a variety of different roles in the body. (Note: So I believe your answer will be 46; 23x2)
The factors are of the form (ax + b)(cx +d)(ex + f) then, the coefficient of x³ is the product of the coefficients of the three x terms, namely ace = 6 The coefficient of x² is the sum of the product of the coefficients of x from 2 brackets multiplied by the number from the remaining bracket. The coefficient of x is the sum of the product of the numbers from two brackets multiplied by the x coefficient from the remaining bracket. The final number is the product of the numbers from the three brackets giving bdf = 4. Some number crunching gives the solution (3x - 1)(x - 4)(2x + 1) Alternatively: We are told that 2x + 1 is a factor. Thus we know: (2x + 1)(ax² + bx + c) = 6x³ - 23x² - 5x + 4 Multiplying out the left gives: 2ax³ + (2b + a)x² + (2c + b)x + c = 6x³ - 23x² - 5x + 4 Thus: 2a = 6 (coefficients of x³) → a = 3 And 2b + a = 2b + 3 = -23 (coefficients of x²) → b = -13 And c = 4 (term not including any x). Thus we now know; 6x³ - 23x² - 5x + 4 = (2x +1)(3x² - 13x + 4) As we are told to factorise it completely, it is likely that the quadratic also factorises. As 3 only has the factor pair 1×3, the quadratic will factorise into (3x + d)(x + e) Thus 3x³ + (3e + d)x + de = 3x² -13x + 4 As the term without any x is positive, d and e must have the same sign. As the coefficient of the x term is negative, both d and e must be negative. Thus, the factor pairs of 4 to consider are (-1)×(-4) and (-2)×(-2). As the coefficient of x is -13 = 3e + d, the values e = -4 and -1 are [fairly] obvious. Thus 6x³ - 23x² - 5x + 4 = (2x +1)(3x - 1)(x - 4)